ANALISA PRODUKTIVITAS KERJA WAKTU DAN BIAYA ALAT BERAT PADA PROYEK MODERNISASI IRIGASI RENTANG KAB. INDRAMAYU - Suminaryati, Sigit Aprilyanto Prabowo; Juliar, Eka (Universitas Majalengka, 2024)
Abstract The Modernization of the Rentang Irrigation Project in Indramayu Regency plays a strategic role in supporting food security and agricultural sector development. The use of heavy equipment is crucial for ensuring the smooth and efficient execution of irrigation work. This study aims to identify the heavy equipment used, the productivity of the heavy equipment, the duration of the activity cycles, and the estimated costs of operating the heavy equipment in the Rentang Irrigation Modernization Project. The research was conducted through direct field observations to collect data on the time required by each piece of heavy equipment during soil reclamation work. This data was then used to calculate the productivity of the heavy equipment. The results showed that the production capacity of the Kubota U50 Excavator is 27.79 m3/hour. The required working duration for the Excavator is 154.23 hours, with an estimated operational cost of Rp. 267,541,273. The production capacity of the Dump Truck is 5.45 m3/hour, with a required working duration of 147.73 hours and an estimated operational cost of Rp. 568,013,231. The production capacity of the Vibro Roller is 63.56 m3/hour, with a required working duration of 337.14 hours and an estimated operational cost of Rp. 112,817,843.